Electrochemistry, spectroelectrochemistry and electrochemical polymerization of titanylphthalocyanines - ÖZKAYA, ALİ RIZA; KOCA, ATIF (PERGAMON-ELSEVIER SCIENCE LTD, 2007)
Detailed electrochemical characterization of tetrakis(2-dimethylaminoethylstilfanyl phthalocyaninato) oxotitanium(IV) and octakis(2-dimethylaminoethylsulfanyl phthalocyaninato) oxotitanium(IV) derivatives has been carried out by the cyclic voltammetry, differential pulse voltammetry, controlled potential chronocoulometry and spectroelectrochemical measurements. Cyclic and differential pulse voltammograms of both complexes are similar, with two metal-based and one ligand-based reduction couples having diffusion controlled reversible one-electron transfer character. Both complexes are polymerized on the working electrode electrochemically during the positive potential sweeps. Spectroelectrochemical measurements confirm the metal and ligand-based assignments of the redox couples. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: spectroelectrochemistry; electrochemical polymerization; cyclic voltammetry; oxotitanium(IV); phthalocyanines; SUBSTITUTED COBALT; PHTHALOCYANINES; MANGANESE; BEHAVIOR